Fabric-Container-Grown Trees - Edward F. Gilman (EDIS, 2003)
Some growers produce trees in fabric containers above ground. The fabric allows air to prune roots and the fabric itself prunes roots. The result is a reduction in the amount of roots circling around the container wall. There is little published information on the tree growth in this production system. This document is ENH870, one of a series of the Environmental Horticulture Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date July 12, 2002.